Factors Determining the Satisfaction of Umrah Pilgrims at Big Tour and Travel Tangerang City - Junaedi, Edy; Maulana, Irwan; Anantasa, Sephia; Khairunnisa, Khalifa T (Indo Consultan Energi, 2025)
The purpose of this study is to determine the influence of service quality and marketing mix on the satisfaction of Umrah pilgrims at PT. Big tour and travel Tangerang City. This study employs independent variables, service quality and marketing mix (X2), and dependent variables, including Umrah pilgrim satisfaction (Y). The population in this study is all big travel Umrah pilgrims. This type of research is descriptive quantitative research with a sample of 80 respondents. The analysis used in this study is the outer model, which includes convergent validity, AVE, discriminant validity, and reliability tests. The inner mode, on the other hand, includes Q-square, GOF, and path coefficient. The study's results showed that the quality of service had a positive impact on the satisfaction of Umrah pilgrims, the marketing mix had a positive impact on their satisfaction, and the combined effect of quality of service and marketing mix had a similarly positive impact on their satisfaction.